Perbedaan Antara Penanganan Luka Snake Bite dengan Insisi dan Tanpa Insisi Terhadap Kecepatan Penurunan Pembengkakan Luka di RSUD Pacitan - Akhmad Rifai; Tri Andriani Cholifah (Poltekkes Kemenkes Surakarta, 2016)
Abstrack: Snake Bite, Incision And Without Incision, Decreasing Speed Of Wound Swelling. Snake bite has different effects, ranging from a simple wound up to life-threatening and even can lead to death. The principle of first aid for snake bite is to avoid the spread of snake poison and to prevent the infection in the bitten part. In the past, the snake bite was treated by using incision while some sources recently stated that the snake bite is not necessary treated by using incision. This study aims to determine The differences between snake bite wound treatment with incision and without incision toward the decreasing speed of wound swelling at RSUD Pacitan. The study design used non-experimental research method : a comparative with retrospective or historical documentary approach. The samples were taken by using total sampling technique. The sum of the samples was 88 documents. They were taken from medical record documents. The statistic test used Chi square with significant value 0.05. The result of the study showed that there were differences between snake bite wound treatment with incision and without incision toward the decreasing speed of wound swelling at RSUD Pacitan in 2009 – 2011.